PERANAN RESIKO KREDIT SEBAGAI VARIABEL MEDIASI TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN DI BEI - Astuti, Diana Dwi; Ningsih, Wiwik Fitria (Magister Manajemen Universitas Islam Malang, 2024)
This research aims to determine the influence of managerial ownership, board of commissioners, audit committee and CAR on financial performance through credit risk. The population in this study used banking companies listed on the Indonesia Stock Exchange for the 2018-2022 period. This research uses a sampling technique, namely purposive sampling, to obtain a sample of 15 companies. The data analysis method uses path analysis. The results of this research show that managerial ownership, board of commissioners and CAR have a direct effect on credit risk. The audit committee has no direct influence on credit risk. Managerial ownership, CAR and credit risk have a direct effect on financial performance. The board of commissioners and audit committee have no direct influence on financial performance. Managerial ownership, board of commissioners, audit committee and CAR have no effect on financial performance through credit risk